Home networking with Universal Plug and Play. - Miller, B.A.
We present an overview of the Universal Plug and Play (UPnPTM ) technology and the UPnP Forum, the multicompany organization that develops parts of the architecture. A technical description of the technology is presented, followed by three illustrative usage cases where it could be applied in home networking environments. Finally, the authors describe the benefits UPnP technology can provide in home networking and discuss potential future work in this area
Keywords: TCP/IP.; UPnP Forum; UPnPT technology; Universal Plug and Play; Web technology; Device protocols; Distributed open networking architecture; Home networking; Multicompany organization; Personal computers